A statistical examination of the link between environmental performance and legal practices: an evaluation of China’s strategies for residual legislative power allocation - Tian, Ze-Hua; Yang, Wu-Song; Tan, Cheng-Xue (Frontiers in Environmental Science, 2023)
This study investigates the correlation between the environmental legal practices of different countries and their environmental performance. It entails an empirical analysis of cross-sectional environmental data collected from 34 countries, including members of the Organization for Economic Cooperation and Development (OECD) and the BRICs nations (Brazil, Russia, India, China, and South Africa). Then the study explores the correlation between a country's environmental performance and both the environmental policy stringency and regulatory enforcement. The findings from this global assessment are subsequently corroborated through an examination of China's environmental time series data spanning a decade, revealing a significant relationship between a country's environmental performance and regulatory enforcement. These results validate the Incomplete Law Theory within the field of environmental law. Moreover, as the second most populous and the third-largest country in terms of land area globally, China's environmental protection strategies and performance play a pivotal role in influencing international environmental outcomes. Consequently, the study conducts a case study on China's environmental legal practices and provides suggestions for enhancing China's allocation strategies of residual legislative power. The study advocates for the optimization of residual legislative power allocation within local environmental law enforcement agencies and a balanced distribution of public and private residual legislative power. This approach reinforces the government's role in strategic formulation.